75 Nurse-led sedation is safe and effective, shortening procedure times, and improving access for selected transcatheter aortic valve implantation (tavi) patients. (6th June 2022) - Browne, Suzannah; Smith, David; Adams, Daniel; Thiruthalil, Sumesh; McGovern, Ian; Mattison, Simon; Panoulas, Vasileios; Kabir, Tito; Davies, Simon; Shannon, Jo; Heng, Ee Ling; Rahbi, Hazim; et al.
Abstract : Background: Aortic Stenosis is the commonest single cardiac valve lesion and Transcatheter Aortic Valve Implantation (TAVI) is now the dominant treatment modality for intervention. The great majority of TAVI procedures are performed under sedation rather than general anaesthetic (GA) however the need for anaesthetist with operating department practitioner support can impose limitations on scheduling and cost thereby limiting access for patients. Method: We implemented a nurse-led TAVI sedation program at a regional centre for selected patients after a dedicated training and mentoring program with anaesthetic support available. From July 2018 until September 2021 inclusive we reviewed consecutive cases with regard to Nurse-led sedation (NLS) vs Anaesthetist-led sedation (ALS). 30-day British Cardiovascular Intervention Society (BCIS) risk estimation, clinical outcomes, procedure duration and length of hospital stay were assessed. Analysis was with the Chi2 test for categorical variables and independent samples t-test for continuous variables. Results: 646 patients were identified with 22 undergoing GA and 624 (97%) undergoing sedation. Of the sedation patients, 212 (34%) underwent NLS and 412 (68%) underwent ALS. The BCIS 30-day risk scores were similar in both groups (NLS 2.2 vs ALS 2.3 p=0.56). Procedural success was similar between the groups (NLS 100% vs ALS 98.5% p=0.07). For the NLS cases, anaesthetic support was sought with telephone discussion in 3 cases (1.4%) and physical attendance in a further 8 cases (3.8%). Clinical outcomes were similar between the groups: (NLS vs ALS) 30-day mortality 1.9% vs 3.7% (p=0.22), Conversion to GA 1.9% vs 2.4% (p=0.67), Vascular access major bleeding 3.3% vs 4.1% (p=0.33), Moderate/severe aortic regurgitation: 4.8% vs 4.2% (p=0.75), Stroke: 4.2% vs 1.7% (p=0.13), New permanent pacemaker implantation 9.4% vs 12.9% (p=0.26). Procedural duration was significantly less with NLS vs ALS (90 mins vs 111 mins p=0.001). Length of hospital stay was similar 3(2–5) days vs 4(2–5) days (p=0.44). Conclusion: This study suggests that an NLS program can be safely introduced into routine TAVI practice with appropriate training and case selection by the Heart Team. Such an approach appears to deliver similar outcomes to ALS with shorter procedural times. It is likely that with increasing experience a greater proportion of TAVI patients will be suitable for NLS. This approach should deliver significant savings in terms of anaesthetic resources alongside more flexible arrangements for scheduling, increased capacity, and improved access for patients. Conflict of Interest: none